2018
DOI: 10.1111/anae.14226
|View full text |Cite
|
Sign up to set email alerts
|

Videolaryngoscopy vs. Macintosh laryngoscopy for double‐lumen tube intubation in thoracic surgery: a systematic review and meta‐analysis

Abstract: Double-lumen intubation is more difficult than single-lumen tracheal intubation. Videolaryngoscopes have many advantages in airway management. However, the advantages of videolaryngoscopy for intubation with a double-lumen tube remain controversial compared with traditional Macintosh laryngoscopy. In this study, we searched MEDLINE, Embase, Cochrane Library and the Web of Science for randomised controlled trials comparing videolaryngoscopy with Macintosh laryngoscopy for double-lumen tube intubation. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 44 publications
(105 reference statements)
7
38
0
Order By: Relevance
“…In (8). Considering only the four studies using GlideScope® videolaryngoscopy of that meta-analysis, our results are consistent with three of these four studies (6,7,16,17).…”
Section: Discussionsupporting
confidence: 84%
“…In (8). Considering only the four studies using GlideScope® videolaryngoscopy of that meta-analysis, our results are consistent with three of these four studies (6,7,16,17).…”
Section: Discussionsupporting
confidence: 84%
“…Rotation manoeuvre more often results in the incorrect position of the DLT. Liu et al concluded that the use of videolaryngoscopes, especially with a hyper-angulated blade for DLT intubation, complicates the already complicated DLT intubation technique through rotation manoeuvres [10]. Our data support the thesis that these sequential rotation manoeuvres are probably the reason why videolaryngoscopy increases the incidence of mispositioning of DLT.…”
Section: Discussionsupporting
confidence: 81%
“…Contrary, a recent meta-analysis in 2018 by Liu et al, showed no difference in intubation time. The metaanalysis included studies with various videolaryngoscopes like Airtraq, McGrath Series 5, McGrath MAC -not all of these provide hyperacute angled devices [10]. Considering only the four studies using GlideScope® videolaryngoscopy included in the meta-analysis, our results are consistent with three of these four studies [8,9,15,16].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the 23 RCTs, we identified a total of 11 different intubating devices, that were further classified and lumped into four groups based on their shapes and features: videolaryngoscope with guiding channel (channeled videolaryngoscope; CV), non-channeled videolaryngoscope (standard videolaryngoscope; SV), videostylet (stylet V), and Macintosh direct laryngoscope (Mc) [ 21 23 ]. We lumped Airtraq, AW, and KVL in the CV group; CEL-100, Glidescope, McGrath, and C-MAC in the SV group; and OptiScope, Shikani, and Trachway in the stylet V group.…”
Section: Resultsmentioning
confidence: 99%